Growth of nanostructures on reduced graphene oxide - Ho, Keng Ee. (2010)
Graphene is known as “the thinnest material in our universe” and exhibits extraordinary properties. In the field of optoelectronics, graphene is regarded as a better conductive substrate replacement over indium tin oxide as it better fulfill the important aspects of being transparent and inexpensive. Zinc oxide (ZnO) nanorods are built on graphene-based substrates via template-free electrodeposition for the use in solar cells. However, the dimensions of ZnO nanorods, which depends on various parameters, still exist as a challenge. Therefore, the purpose of this project is to study the influence of deposition potential on the growth density and crystallinity of ZnO nanorods on graphene-based substrates.